Antibiotic susceptibility of Escherichia coli strains in neonatal alpacas with and without diarrhoea - Barrios-Arpi, Manuel (2016)
The present study aimed to determine the antimicrobial susceptibility of Escherichia coli isolates in neonatal alpacas with and without diarrhea in peasant communities in Lachocc, Huancavelica, Peru. Rectal swabs from alpacas with diarrhoea (n=95) and from apparently normal alpacas (n=60) of 1 to 2 months of age were analysed. The results showed that 48.4% (46/95) and 60% (36/60) of samples from animals with and without diarrhea were positive to E. coli. The isolates were sensitive to most of the antibiotics, especially trimethoprim (98%), gentamicin (95%) and fosfomycin (88%). The exception was nitrofurantoin, whose strains showed low susceptibility (8.3%).